THE IMPACT OF LANGUAGE OF INSTRUCTION ON QUALITY OF SCIENCE AND ENGINEERING EDUCATION IN LIBYA: QUALITATIVE STUDY OF FACULTY MEMBERS - Tamtam, Abdalmonem; Gallagher, Fiona; Naher, Sumsun; Olabi, Abdul (European Scientific Journal, ESJ, 2013)
The qualitative study aimed to investigate teaching staff views on language of instruction impact on the quality of education in two Libyan universities, where faculties of science and engineering at University of Al-Jabal Al-Garbi use Arabic as medium of instruction , and faculties of science and engineering at Nasser International University use English as medium of instruction. The participants in the study were five faculty members from each university teaching different science and engineering fields interviewed regarding their views on using Arabic only, English Only or Arabic-English Bilingualism as medium of education. The Findings of the interviews revealed that teachers of both the cases have almost similar views with slight variations regarding all the three medium of instructions. According to participants of both cases, English would have bad impact on the students’ academic performance for this reason Participants of case 1 think that students do not like English. On other hand respondents of Case 2 students like English despite their poor performance, as they know that, English is the only gateway for going Global. Participants of both cases stated though students like Arabic and it is easy for them to study in Arabic. All participants mentioned that use of Arabic results in lack of the job opportunities. In addition, the lack of academic materials and resources is an issue of Arabic Medium Instruction. Arabic-English Bilingualism seems to be the best solution for taking first step towards globalization. Many participants of both cases suggested Arabic-English Bilingualism as a first step towards globalization.